Psychosocial support and wellbeing of orphans and vulnerable children (OVC) in the context of HIV/AIDS: a case study of early childhood development and education (ECDE) centres in Nairobi, Kenya - Nyakundi, Linet Imbosa (My University, 2017)
Psychosocial support and wellbeing of orphans and vulnerable children (OVC) in sub-Saharan Africa receive a lot of attention globally. However, great concerns still persist due to a multiplicity of factors that affect the children’s quality of life. This study examines experiences of psychosocial support and wellbeing of these children in Nairobi, Kenya. While there are few existing studies on the effects of HIV and AIDS on OVC in Kenya, most focus on OVC in primary schools and high schools leaving out infants and preschool aged OVC, as is the case in sub-Saharan Africa. Thus, information that details psychosocial experiences and wellbeing of OVC in preschools in Kenya is lacking. This study focused on OVC aged between 5 and 7 years old within a resilience theoretical perspective; investigated their lived experiences, risk exposure, support structures and other adaptive experiences. A total of 57 participants (45 were children and 12 teachers) from ECDE centres in Nairobi County were purposively sampled for the study. Multiple methods utilised included: visual stimulus illustrations, face-to-face and conversational interviews, thematic drawings, focus group discussions questionnaires and infrastructural and supportive resource assessment. Thematic content analysis (TCA) which was informed by phenomenological hermeneutic approach was used to analyse data. Findings consistently showed that, OVC were not only susceptible to numerous risk experiences due to environmental and care factors at home, but also on their way to and from school, and within ECDE centres. Nonetheless, ECDE centres exposed them to cognitive skills, social networks, safety, alternative care, primary health services, nutrition and resilience nurturance. These findings indicate the crucial role of having a collective action in reduction of adverse experiences and improving resources to empower the OVC in urban ECDE centres. Directions for further research could focus on expanded population-based studies examining poverty, malnutrition, resilience and coping resources among preschool children living with, and affected by HIV and AIDS, using creative multiple qualitative approaches. A more critical understanding on variations in sexes is equally important in intervention strategies for this group of OVC.
Thesis submitted in fulfillment of the requirements for the degree of Doctor of Philosophy in Psychology, School of Human and Community Development University of the Witwatersrand, May 2017
Keywords: Orphans--Kenya--Nairobi; AIDS (Disease) in children--Kenya--Nairobi; AIDS (Disease)--Social aspects--Kenya--Nairobi